Awareness of Basic Life Support among Egyptian Medical Students; a Cross-Sectional Study - Ghanem, Esraa; Elgazar, Muhammad; Oweda, Khaled; Tarek, Hussien; Assaf, Fathy; Wanees, Mostafa; Elgebaly, Ahmed; Abushouk, Abdelrahman Ibrahim (Archives of Academic Emergency Medicine, 2018)
Introduction:Â It is important for all medical and paramedical staff to be aware of basic life support (BLS) maneuvers. In this study, we aimed to evaluate the level of BLS awareness among Egyptian medical students. Methods:Â The level of BLS knowledge was assessed using a validated questionnaire and the results were analyzed using an answer key, prepared from the Advanced Cardiac Life Support (ACLS) manual. We used the Student’s t-test to analyze the association between awareness level and year of study, previous BLS training and practical experience. Results:Â A total of 823 medical students with the mean age of 20.3 Â± 2.7 years, from Al-Azhar medical schools completed the questionnaire (463 and 360 in academic and clinical years, respectively). About 72% and 84% of students failed to recognize the proper point of chest compression in adults and infants, respectively. Moreover, the majority (80%) did not know how to give rescue breathing in infants. Only 18% of students correctly identified early signs of shock and only 22% knew how to help patients with myocardial infarction. Being in clinical years, previous BLS training or practical experience were significantly associated with higher BLS knowledge scores (pÂ < 0.001). Conclusion:Â The level of BLS awareness among Egyptian medical students is generally poor. Introduction of regular BLS courses into the undergraduate curriculum is a must to increase the level of BLS knowledge among Egyptian future physicians.